Transcriptomic configuration of mouse brain induced by adolescent exposure to 3,4-methylenedioxymethamphetamine - Eun, Jung Woo; Kwack, Seung Jun; Noh, Ji Heon; Jung, Kwang Hwa; Kim, Jeong Kyu; Bae, Hyun Jin; Xie, Hongjian; Ryu, Jae Chun; Ahn, Young Min; Min, Jin-Hye; Park, Won Sang; Lee, Jung Young; et al. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2009)
The amphetamine derivative (+/-)-3,4-methylenedioxymethamphetamine (MDMA or ecstasy) is a synthetic amphetamine analogue used recreationally to obtain an enhanced affiliative emotional response. MDMA is a potent monoaminergic neurotoxin with the potential to damage brain serotonin and/or dopamine neurons. As the majority of MDMA users are young adults, the risk that users may expose the fetus to MDMA is a concern. However, the majority of studies on MDMA have investigated the effects on adult animals. Here, we investigated whether long-term exposure to MDMA, especially in adolescence, could induce comprehensive transcriptional changes in mouse brain. Transcriptomic analysis of mouse brain regions demonstrated significant gene expression changes in the cerebral cortex. Supervised analysis identified 1028 genes that were chronically dysregulated by long-term exposure to MDMA in adolescent mice. Functional categories most represented by this MDMA characteristic signature are intracellular molecular signaling pathways of neurotoxicity, such as, the MAPK signaling pathway, the Wnt signaling pathway, neuroactive ligand-receptor interaction, long-term potentiation, and the long-term depression signaling pathway. Although these resultant large-scale molecular changes remain to be studied associated with functional brain damage caused by MDMA, our observations delineate the possible neurotoxic effects of MDMA on brain function, and have therapeutic implications concerning neuro-pathological conditions associated with MDMA abuse. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: WNT SIGNALING PATHWAY; GENE-EXPRESSION; AXON TERMINALS; MDMA ECSTASY; HEPATOCELLULAR-CARCINOMA; NEUROTOXICITY; RAT; FOREBRAIN; DOPAMINE; MICE